1982
DOI: 10.1042/bj2080205
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a direct role of phospholipid methylation in stimulus-secretion coupling and control of adenylate cyclase in guinea-pig and rat parotid gland

Abstract: The present study was undertaken to investigate a possible involvement of phospholipid methyltransferases in the coupling of receptor-mediated stimulation to secretion. Phospholipid methyltransferases were assayed in isolated parotid acini in the presence of carbamoylcholine or isoprenaline. Carbamoylcholine reduced the incorporation of methyl groups into phospholipids, whereas isoprenaline showed no effect. Amylase secretion stimulated either by carbamoylcholine or by isoprenaline could not be affected by inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…This result further suggests that methyltransferase activity and ligandreceptor interactions occur. Our results are similar to those of Padel et al [12] and Colard et al [29] in that basal and NaF-stimulated adenylate cyclase activity were not altered by a methyltransferase inhibitor. Contrary to our findings, Padel et al found that the activity of receptor-stimulated adenylate cyclase in isolated parotid microsomal membranes was not inhibited or stimulated by S-adenosylhomocysteine or by the addition of S-adenosylmethionine, and amylase secretion was not inhibited by inhibitors of methyltransferase.…”
Section: Discussionsupporting
confidence: 94%
“…This result further suggests that methyltransferase activity and ligandreceptor interactions occur. Our results are similar to those of Padel et al [12] and Colard et al [29] in that basal and NaF-stimulated adenylate cyclase activity were not altered by a methyltransferase inhibitor. Contrary to our findings, Padel et al found that the activity of receptor-stimulated adenylate cyclase in isolated parotid microsomal membranes was not inhibited or stimulated by S-adenosylhomocysteine or by the addition of S-adenosylmethionine, and amylase secretion was not inhibited by inhibitors of methyltransferase.…”
Section: Discussionsupporting
confidence: 94%
“…Guinea pig parotid gland acini were prepared as described [5]. For subcellular fractionation the acinar cells were washed 3 times in medium A (130 mM KCI, 2 mM MgC12, 2 mM K phosphate, 1 mM dithiothreitol, 1 mM benzamidine, 20 mM Hepes-KOH, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Receptor-mediated release of calcium from intracellular pools by inositol 1,4,5-trisphosphate (Ins (1,4,5)P3) has been shown to occur in many different cell types. More recently, it has been reported that 5' -GTP can also stimulate the release of endogenous calcium.…”
Section: Introductionmentioning
confidence: 99%
“…the conversion of phosphatidylethanolamine into phosphatidylcholine (Hirata et al, 1979;Hirata & Axelrod, 1980). However, this is controversial since in different cell types it has been shown that phospholipid methylation is not directly related to adenylate cyclase activities (Colard & Breton, 1981;Padel et al, 1982) and is not ©D The Macmillan Press Ltd 1987 involved with whole cell activation (Randon et al, 1981;Schanche et al, 1982;Moore et al, 1982;Benyon et al, 1986). We previously demonstrated that platelet activation can be inhibited by the methylation inhibitors (Randon et al, 1981;, by mechanisms other than interference with phospholipid methylation, such as protein methylation (reviewed by O'Dea et al, 1981).…”
Section: Introductionmentioning
confidence: 99%